« Alli homini è prohibita una cosa, a prencipi è permessa, alle donne sono prohibite altre cose ». Imposture des religions, différences sociales et différences de genres à Venise au xviie et xviiie siècle - Federico Barbierato (Les Dossiers du GRIHL)
The essay examines seventeenth- and eighteenth-century Venetian Inquisition trials and focuses on the inquisitors’ role in the construction of gender identity. In these trials many women constructed a heterodox and unbelieving identity, often equipped with languages (at least partially) different from the male ones. What characterized the gender-based interpretation of heterodoxy had less to do with beliefs than with the attitude displayed by repressive institutions. Women’s words appeared as less dangerous, less indicative of a link with thought – women were considered to be alien or little inclined to that. For this reason, the pronunciation by men and women of the same propositions had different significance in the eye of the inquisitors: women’s words appeared less credible, less able to persuade, therefore patronizingly considered as less dangerous. The outcome was a curious short circuit. On the one side, learned libertinism used women as part of a negative comparison, by assimilating them to the ignorant and credulous hoi polloi. On the other side, inquisitors decided not to prosecute – or to prosecute to a limited extent only  – women stained with speech tinged with unbelief and heterodoxy.